Physical-chemical-enzymatic pretreatment process for bioconversion of kitchen waste into fermentable sugar as a feedstock for bioethanol production - Hafid, Halimatun Saadiah (2017)
Sustainable conversion of municipal solid waste (MSW) into bioethanol taking into account the availability of the organic fraction of the waste which is kitchen waste that contains high carbohydrate, soluble sugar, starch, protein, lipid and other materials. It can be converted to fermentable sugar via hydrolysis and saccharification process which is still recognized as a rate-limiting step of the conversion process of kitchen waste to bioethanol. Hence, this study aimed to evaluate the physical, chemical, enzymatic and combination of pretreatment at enhancing the hydrolysis and maximizing the yield of fermentable sugar produced. This study is divided into three parts of pretreatment by (1) Hydrothermal and dilute acid; 2) Enzymatic pretreatment; 3) Combination of physical-chemical and enzymatic pretreatment, and followed by 4) Production of bioethanol using saccharified kitchen waste using locally isolated yeasts; Saccharomyces cerevisiae, Candida parasilosis, and Lachancea fermentati. Initially, hydrolysis of kitchen waste by hydrothermal and dilute acid systems were carried out by varying the reaction temperatures (80, 90, 100C) hydrolysis reactant; hot distilled water (hydrothermal), hydrochloric acid (HCl) and sulphuric acid (H2SO4) at different concentrations (0.5 - 2.0%) and evaluated using kinetic modelling approach by gPROMS software. A significant improvement of fermentable sugar production by 40.6% was observed at optimize condition of 1.5% HCl and 44.9% using 1.0% H2SO4 at 90C as compared to hydrothermal pretreatment. The hydrolysis rate coefficient at 90C for fermentable sugars production, kr=1, was 0.68 gL-1min-1 for hydrothermal system and 1.61 and 1.88 gL-1min-1 in HCl and H2SO4 catalysed system, respectively. Enhanced hydrolysis of kitchen waste for fermentable sugar production was achieved by hydrothermal and dilute acid pretreatment. Meanwhile, response surface methodology (RSM) technique is adopted in enzymatic pretreatment for a prediction of optimal condition of independent variables (pH, temperature, glucoamylase activity, kitchen waste loading and hydrolysis time) on fermentable sugar production and degree of saccharification. Quadratic RSM predicted maximum fermentable sugar production of 62.79 g/L and degree of saccharification (59.90%) at the optimal conditions; pH 5, temperature 60°C, glucoamylase activity of 85 U/mL and utilized 70 g/L of kitchen waste as a substrate at 10 hours hydrolysis time. The verification experiments successfully produced 65.71 ± 0.7 g/L of fermentable sugar with 55.3 ± 0.4% degree of saccharification which 31.4% higher than non-optimized condition indicating that the developed model was successfully used to predict fermentable sugar production at more than 90% accuracy. The experiment was continued by applying single and combination pretreatments by hydrothermal, mild acid pretreatment of HCl and H2SO4 and with enzymatic hydrolysis by glucoamylase. The maximum total fermentable sugar produced after combination pretreatment by 1.5% HCl and glucoamylase produced 94.45 g/L of fermentable sugar consisted of 93.25 g/L glucose, 0.542 g/L sucrose, 0.348 g/L maltose, and 0.321 g/L fructose. An increase of 55.8% and 91.8% of fermentable sugar production was obtained by comparing with single glucoamylase and 1.5% HCl pretreatment, respectively. From FTIR analysis, the decrease of aliphatic absorbance bands of polysaccharides at 2851 and 2923 cm-1 and the increase on structures of carbonyl absorbance bands at 1600 cm-1 reflects the progress of the kitchen waste hydrolysis to fermentable sugars. For total cost and profit estimation, combination of 1.5% HCl and glucoamylase pretreatment was the most profitable process as the minimum selling price of glucose was USD 0.101/g kitchen waste. The combination pretreatment method was successfully enhance the production of fermentable sugar from kitchen waste. Production of fermentable sugar using acid-pretreated and enzymatic hydrolysis of kitchen waste was then conducted in 2L of bioreactor. The results suggested that a significant increase in fermentable sugar production to 103.4 ± 0.04 g/L (2.04-folds) with conversion efficiency of 86.8% was observed via sequential acid-enzyme pretreatment as compared to dilute acid (42.4%) and glucoamylase enzyme (50.6%), respectively. An increased in total fermentable sugar to 150.5 ± 0.11 g/L which consist of glucose (128.47 g/L), fructose (6.24 g/L), sucrose (5.59 g/L) and maltose (10.18 g/L) was successfully recovered after downstream processing. The fermentable sugars obtained were subsequently converted to bioethanol by locally isolated yeasts; Saccharomyces cerevisiae, Candida parasilosis, and Lachancea fermentati produce ethanol yield ranging from 0.45 g/g to 0.5 g/g after 24 h which was equivalent to 82.06 - 98.19% of conversion efficiency based on theoretical yield that was comparable with using commercial glucose. The finding indicates that kitchen waste can be considered as a promising substrate for bioethanol production.